Of Languages and Epistemologies: Reflections of a Graduate International Student on the Road to Becoming a Researcher - Colombo, Laura (Violeta) (Journal of International Students, 2014)
It is late at night, after working all day on my postdoctoral research I am trying to wind down while drawing and jotting down thoughts in my notebook. I am at the living room/office of my apartment in Buenos Aires, the city where I was born and left when I was 26 years old to pursue my graduate studies in the United States of America where for almost nine years I was an international graduate student. So here I am again back in my country, thinking about the intersections between epistemology and language that I have come across on this endless road to becoming a researcher and how I have dealt with these junctures.